2019
DOI: 10.1038/s41467-018-08037-5
|View full text |Cite
|
Sign up to set email alerts
|

Control of triboelectric charges on common polymers by photoexcitation of organic dyes

Abstract: Triboelectric charging of insulators, also known as contact charging in which electrical charges develop on surfaces upon contact, is a significant problem that is especially critical for various industries such as polymers, pharmaceuticals, electronics, and space. Several methods of tribocharge mitigation exist in practice; however, none can reach the practicality of using light in the process. Here we show a light-controlled manipulation of triboelectric charges on common polymers, in which the tribocharges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…Important phenomena such as triboelectric charging ( Matsusaka et al, 2010 ; Cezan et al, 2019 ) and the mechanical generation of exposed surfaces ( Belenguer et al, 2016 ; Schneider-Rauber et al, 2021 ) or defects are equally likely to occur in inorganic, organic, and polymeric compounds. It is probable that such phenomena involving defect formation ( Boldyrev, 1973 ; Yelsukov et al, 2013 ) play a central role in most solid-state mechanochemical transformations, even if they are often overlooked and subsumed by explanations of “mere mixing”.…”
Section: What Is In a Name?mentioning
confidence: 99%
See 1 more Smart Citation
“…Important phenomena such as triboelectric charging ( Matsusaka et al, 2010 ; Cezan et al, 2019 ) and the mechanical generation of exposed surfaces ( Belenguer et al, 2016 ; Schneider-Rauber et al, 2021 ) or defects are equally likely to occur in inorganic, organic, and polymeric compounds. It is probable that such phenomena involving defect formation ( Boldyrev, 1973 ; Yelsukov et al, 2013 ) play a central role in most solid-state mechanochemical transformations, even if they are often overlooked and subsumed by explanations of “mere mixing”.…”
Section: What Is In a Name?mentioning
confidence: 99%
“…11,186 This represents a critical difference between inorganic and organic 'solid state' transformations under mechanochemical action. 133 Important phenomena such as triboelectric charging 158,187 and the mechanical generation of exposed surfaces 188,189 or defects are equally likely to occur in inorganic, organic, and polymeric compounds. It is probable that such phenomena involving defect formation 190 play a central role in most solid state mechanochemical transformations, even if they are often overlooked and subsumed by explanations of "mere mixing".…”
Section: Figure 3|mentioning
confidence: 99%
“…During the motion process (sliding or separation), opposite charges on the surface of materials are produced, whose amount will significantly increase if the surface area increases and changes according to the different composition and structure of materials [24,25]. Several studies have been conducted to understand the charge formation mechanisms, and they also provided the basis for measurements standards [26][27][28]. In another work, Zou et al [29] demonstrated how to measure triboelectricity by using several polymers as examples.…”
Section: Introductionmentioning
confidence: 99%
“…[ 27 ] To this end, the triboelectric series is widely used to choose appropriate triboelectric materials. [ 7 ] A material found at the bottom of the series, when in friction with a material found at the top of the series, will acquire more electrons. The further the distance between the two materials in the series, the greater is the charge transfer that occurs in the TENG.…”
Section: Dp‐tengsmentioning
confidence: 99%
“…In recent years, personal electronic devices have become smaller and more portable in a smart fashion. [1] Researchers are striving to develop smaller-sized wearable [2] and implantable sensors [3] to monitor physiological and environmental signs including, but not limited to, pressure, [4] proximity, [5] motion, [6] chemistry, [7] optics, [8,9] biologics, [10] humidity, [11] temperature, [12] gas, [13] acoustics, [14] neural, [15] and cochlear. [16] In the near future, on average, each person will carry dozens of such small electronic devices, which will require a portable power source.…”
Section: Introductionmentioning
confidence: 99%